SERVICE LEARNING IN STRENGTHENING BRANDING AND INNOVATION OF TRADITIONAL DODOL PRODUCTS, MELAKA, MALAYSIA - Rachmad Chartady; Satriadi Satriadi; Reza Ramadhania; Teguh Widodo; Darsih Darsih; Putri Dimaz Meynah (PT. Jurnal Center Indonesia Publisher, 2026)
This service responds to the challenges of traditional dodol entrepreneurs in Melaka, Malaysia: weak branding strategies, lack of product innovation, and low competitiveness in the midst of the modern food industry. Using a participatory service learning approach based on qualitative methods (in-depth interviews, field observations, FGDs), students are actively involved in business assistance including packaging design, flavor variant development, improvement of hygiene standards, and the use of digital media for promotion. This program aims to strengthen the Melaka dodol brand identity, encourage product innovation, and increase the capacity of MSME actors. Its contribution lies in the university-community collaboration model that strengthens the local economy while preserving culinary heritage through the documentation of cultural values. The results show an improvement in branding quality, more attractive packaging, the emergence of variant innovations, and an increase in the digital marketing capabilities of business actors. This activity also strengthens student-community social relations and opens up opportunities for community innovation hubs for sustainable collaboration. The findings affirm the effectiveness of service learning as an empowerment strategy that integrates cultural preservation with the strengthening of the local economy, as well as making a theoretical-practical contribution to community-based entrepreneurship.